COGNITIVE DEVELOPMENT AND VARIABLE CONTROL IN SCIENTIFIC REASONING: ASSESSING INDONESIAN STUDENTS' ENVIRONMENTAL CHANGE UNDERSTANDING VIA LAWSON CLASSROOM TEST - Nurul Fajryani Usman; Nur Mustaqimah; Herinda Mardin (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
This study aims to assess the scientific reasoning abilities of Class XI IPA students at SMA Negeri 3 Gorontalo in relation to environmental change materials. The background of this study is based on the low scientific reasoning skills of students, which have implications for suboptimal critical thinking, problem-solving, and mastery of scientific concepts. The research method employs a quantitative descriptive approach using the Lawson Classroom Test of Scientific Reasoning (LCTSR) test instrument, which comprises six indicators of scientific reasoning: proportional reasoning, probabilistic reasoning, correlational reasoning, variable identification and control, volume conservation, and hypothetico-deductive reasoning. The research sample consisted of 35 students randomly selected from Class XI Biology primary majors at SMA Negeri 3 Gorontalo. The results showed that most students were at the transitional operational stage (54%), while 41% were still at the concrete operational stage, and only 5% had reached the formal operational stage. Overall, the average scientific reasoning ability of students was in the sufficient category (41%). The probabilistic indicator achieved the highest score (61%, good), while variable identification and control achieved the lowest score (7%, poor). The contribution of this study is to provide a clear picture of students' scientific reasoning abilities based on each LCTSR indicator. The learning implications of these findings are the need for more instruction that gradually trains scientific thinking, particularly in determining variables, controlling variables, and drawing conclusions based on data